Iplementasi Strategi Every One Is a Teacher Here Untuk Meningkatkan Ketrampilan Berbicara Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas V Semester 1 SDN 1 Sendang Todanan Blora Tahun Ajaran 2015/2016 - MUSTOFA, ALI, Drs. Suwarno, SH., M. Pd (2015)
This study was motivated by the low skills of speaking students. The purpose of this research is to improve student learning outcomes in the skills of speaking in class V SDN 1 Spring District of Todanan Blora. This research was conducted using Action Research (PTK) by the method of discussion.This research was conducted in two cycles with 3 meeting. Subjects were students of class V SD Negeri 1 Spring District of todanan Blora academic year 2015/2016 totaling 28 students. Managing data in this study by analyzing data qualitatively. Learning outcomes as quantitative data obtained from the results of group work and individual evaluation of the test results to see an increase in the skills of students to the concept of matter speaking skills. Secondary data include data on students' understanding of the learning outcomes of students, pratindakan, lesson plan, syllabus and curriculum derived from the documents held by teachers and school. Data collected through the practice tests, observations, consider the study and observation. To test the validity of the data is done by triangulation. From the analysis of the data found that student learning outcomes before held the action is 11 students (39.28%) thoroughly studied and 17 students (60.71%) has not been thoroughly studied. In the first cycle were 24 (85.71%) students have thoroughly studied and 4 students (14:28%) has not been thoroughly studied. In the second cycle learning completeness reached 96.42% at 27 students have been thoroughly studied.Beradasarkan the data above, shows that the improvement of learning subjects Indonesian subject speaking skills have produced a satisfactory value, thus the improvement of learning has been completed. Keywords: every one is a techer here, speaking skills.